2019
DOI: 10.1177/0049475519854623
|View full text |Cite
|
Sign up to set email alerts
|

Libman-Sacks endocarditis in a Bangladeshi patient suffering from rhupus

Abstract: Libman-Sacks endocarditis (LSE) is one of the most characteristic cardiac lesions in systemic lupus erythematosus (SLE). Patients may remain asymptomatic, while symptomatic patients often suffer with systemic emboli. These commonly test positive for anti-phospholipid antibody (aPA). The association of LSE with an overlap of rheumatoid arthritis (RA) and lupus (also known as ‘rhupus’) is rare. We report such a patient, who had been diagnosed as having RA seven years before and had suffered an acute ischaemic st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 4 publications
(8 reference statements)
0
2
0
Order By: Relevance
“…In the most recent systematic review, 100 of 287 cases of rheumatoid arthritis had renal involvement, compared to 12 cases of vasculitis and two case reports of CNS vasculitis. [10,14,15] (Table 3). In the same systematic review, 202 of 287 patients were identified with hematological abnormalities, but only a few instances showed autoimmune hemolytic anemia, the majority of which had favorable outcomes [10,[16][17][18][19][20][21][22] (Table 3).…”
Section: Discussionmentioning
confidence: 99%
“…In the most recent systematic review, 100 of 287 cases of rheumatoid arthritis had renal involvement, compared to 12 cases of vasculitis and two case reports of CNS vasculitis. [10,14,15] (Table 3). In the same systematic review, 202 of 287 patients were identified with hematological abnormalities, but only a few instances showed autoimmune hemolytic anemia, the majority of which had favorable outcomes [10,[16][17][18][19][20][21][22] (Table 3).…”
Section: Discussionmentioning
confidence: 99%
“…Postmortem findings have demonstrated that therapy with heparin also reduces the risk of cerebral infarction in patients with NBTE associated with malignancy [10]. A recent study in patients with malignancy and acute thromboembolism demonstrated low-molecular-weight heparin to be more effective than warfarin in reducing the risk of recurrent thromboembolism in NBTE [11][12][13][14]. Furthermore, anticoagulation should be continued indefinitely in patients with NBTE because of the risk of recurrent thromboembolism following discontinuation of this therapy.…”
Section: Managementmentioning
confidence: 99%